Reflexivity, Expectations Feedback and almost Self-fulfilling Equilibria: Economic Theory, Empirical Evidence and Laboratory Experiments - Cars Hommes (Tinbergen Institute, 2013)
We discuss recent work on bounded rationality and learning in relation to Soros' principle of reflexivity and stress the empirical importance of non-rational, almost self-fulfilling equilibria in positive feedback systems. As an empirical example, we discuss a behavioral asset pricing model with heterogeneous expectations. Bubble and crash dynamics is triggered by shocks to fundamentals and amplified by agents switching endogenously between a mean-reverting fundamental rule and a trend-following rule, based upon their relative performance. We also discuss learning-to-forecast laboratory experiments, showing that in positive feedback systems individuals coordinate expectations on non-rational, almost self-fulfilling equilibria with persistent price fluctuations very different from rational equilibria. Economic policy analysis may benefit enormously by focussing on efficiency and welfare gains in correcting mispricing of almost self-fulfilling equilibria.
Keywords: D84; D83; E32; C92; 330; Expectation feedback; self-fulfilling beliefs; heuristic switching model; experimental macroeconomics